2023
DOI: 10.3390/info14090508
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Approach for Predictive Healthcare Process Monitoring

Ulises Manuel Ramirez-Alcocer,
Edgar Tello-Leal,
Gerardo Romero
et al.

Abstract: In this paper, we propose a deep learning-based approach to predict the next event in hospital organizational process models following the guidance of predictive process mining. This method provides value for the planning and allocating of resources since each trace linked to a case shows the consecutive execution of events in a healthcare process. The predictive model is based on a long short-term memory (LSTM) neural network that achieves high accuracy in the training and testing stages. In addition, a frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…This highlights the importance of involving hospital patient data in comprehensive and evidence-based disease prevention planning. Hospital patient data have been integrated with public health data to support integrated health policies [22][23][24]. They showed that hospital patient data should be integrated with public health data to provide a more comprehensive understanding of public health issues and aid in designing integrated, holistic, and effective health policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This highlights the importance of involving hospital patient data in comprehensive and evidence-based disease prevention planning. Hospital patient data have been integrated with public health data to support integrated health policies [22][23][24]. They showed that hospital patient data should be integrated with public health data to provide a more comprehensive understanding of public health issues and aid in designing integrated, holistic, and effective health policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research undertakes the formidable challenge of seamlessly integrating emotional intelligence into the fabric of robot teachers, with a deliberate emphasis on the significance of understanding and appropriately responding to students' emotions. By doing so, it seeks to enhance the effectiveness of the teaching and learning experience, recognizing that the emotional context within the educational setting plays a crucial role in shaping the overall success of the educational process [6], [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%